PERAN GURU DALAM PENGUATAN PROFIL PELAJAR PANCASILA DI SD NEGERI KASIHAN - Ari Wibowo; Henida Widiastuti (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
By emphasizing the role that teachers play in putting the Pancasila Student Profile into practice for future generations, this research aims to clarify how the Pancasila Student Profile is applied. This study also aims to outline the difficulties and solutions associated with putting the Pancasila Student Profile into practice. The methodology in this study is qualitative. The principal, teachers, and students at SD N Kasihan served as the research's data sources. the methods of observation and interviewing used to gather research data and the Grounded Theory method applied to qualitative data analysis methods. The validity of the data was checked by means of technical triangulation and source triangulation. From the results of this research, it can be concluded that the teacher's role in strengthening the profile of Pancasila students at SD N Kasihan is optimal, as evidenced by the routine activities carried out every Saturday. This activity concerns the six elements of the Pancasila Student Profile which are implemented through the teacher's role as a creative designer, mentor, and evaluator.